Crystal structure of catena-poly[diaqua-bis(μ2-1,3-di(1H-imidazol-1-yl)propane-κ2 N:N′)cobalt(II)] dinitrate, C18H28N10O8Co - Liu Jie; Jiang Peng; Yang Xiao-Ming; Lu Jiu-Fu (Zeitschrift für Kristallographie - New Crystal Structures)
C18H28N10O8Co, monoclinic, P21/c (no. 14), a = 9.2248(5) Å, b = 13.3140(8) Å, c = 10.6132(6) Å, β = 109.348(7)°, V = 1229.89(13) Å3, Z = 2, R gt(F) = 0.0336, wR ref(F 2) = 0.1078, T = 293(2) K.